Kulish V. S. Interpretation of stylistically-marked nominations of silence in English and Russian poetical discourse - Kulish V. S. (Philological Treatises, 2020)
This article deals with the interpretation of stylistically-marked nominations of silence in poetical discourse (English and Russian). We distinguish stylistically-marked lexical nominations which correlate with poetical images of silence. Attention is focused upon such emotional markers as lexical reiteration, personification, metaphor, simile and their interpretation in target language.